SPECIFICS TAIL RISKS THAT THREATEN ECONOMIC SECURITY OF INDUSTRIAL ORGANIZATIONS - A. Savin (Вестник университета, 2017)
This article discusses examples of tail risks of industrial companies. Consistently analyzes the risks of bankruptcy organization, the loss of material and technical base of the organization, reset its revenue due to the loss of customers, staff exodus, inconclusive research and development. The conclusion about the need to manage tail risk and provides recommendations to counter them at the level of the organization.